Almonertinib-induced interstitial lung disease in an NSCLC patient co-harboring EGFR Ex19del mutation and MET de novo amplification: a case report and literature review - Yang, Wenjing; Shi, Lin; Wang, Hao; Li, Ying; Ji, Xingyu; Li, Hongjin; Yang, Guowang; Xu, Weiru (Frontiers in Oncology, 2025)
Lung cancer patients co-harboring EGFR Ex19del mutation and MET de novo amplification is extremely uncommon. Thus, the optimal therapeutic strategies, treatment-related complications, and prognosis for such patients remain unclear. Herein, we describe a case of patient co-harboring EGFR Ex19del mutation and MET de novo amplification who presented targeted (almonertinib)-induced interstitial lung disease (ILD). We propose that patients with EGFR Ex19del mutation and MET de novo amplification may benefit more from dual-targeted therapy than pemetrexed and carboplatin chemotherapy along with bevacizumab. However, dual-targeted therapy may increase the risk of ILD, so it is important to be alert to targeted-induced ILD, and unexplained fever may be an early warning signal for targeted-induced ILD, especially almonertinib-induced ILD. Timely intervention is needed to avoid greater harm when ILD occurs and, when ILD is effectively controlled, seize the opportunity to rechallenge the dual-targeted therapy may contribute to a better prognosis. In addition, the patients with targeted-induced ILD in the past need more rigorous monitoring and follow-up in the process of rechallenging the targeted drug therapy.